The RIC Potential Amid Growing Indian-Chinese - E. Arapova (Международная аналитика)
The article aims at assessing the potential of trilateral cooperation of Russia, China and India amid growing geopolitical and economic contradictions between India and China in recent years, as well as the role of Russia in strengthening trilateral partnership. Despite the unfavorable dynamics in latent conflicts resolution, the high economic interdependence and importance of the three countries for each other push them to search for opportunities for mutually beneficial constructive partnership on an equal footing.The study demonstrates the low potential of trilateral cooperation. At the same time, cooperation at the multilateral level can be much more effective: within the SCO, BRICS and, quite possibly, "BRICS+", if this initiative is implemented in accordance with the Russian approach, with the participation of all members of the BRICS-driven integration blocks. At the same time, Russia can take on the role of moderator of the Indian-Chinese contradictions, concentrating efforts primarily in the economic area to achieve higher efficiency in the short- and medium term.